2004
DOI: 10.1177/026119290403200409
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Assays with Fish Cells as an Alternative to the Acute Lethality Test with Fish

Abstract: In ecotoxicology, in vitro assays with fish cells are currently applied for mechanistic studies, bioanalytical purposes and toxicity screening. This paper discusses the potential of cytotoxicity assays with fish cells to reduce, refine or replace acute lethality tests using fish. Basal cytotoxicity data obtained with fish cell lines or fish primary cell cultures show a reasonable to good correlation with lethality data from acute toxicity tests, with the exception of compounds that exert a specific mode of tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Thus, DarT will likely play an important role in the development of alternatives to fish tests within the next years. An implementation at the regulatory level as substitute for a fish test has not yet been accomplished with fish or mammalian cultured cells (Kilemade and Quinn, 2003;Segner, 2004). However, numerous studies can be found that allow their potential and current limitations with regard to replacing fish tests to be evaluated.…”
Section: Current Status Of In Vitro Alternatives To Fish Testsmentioning
confidence: 99%
“…Thus, DarT will likely play an important role in the development of alternatives to fish tests within the next years. An implementation at the regulatory level as substitute for a fish test has not yet been accomplished with fish or mammalian cultured cells (Kilemade and Quinn, 2003;Segner, 2004). However, numerous studies can be found that allow their potential and current limitations with regard to replacing fish tests to be evaluated.…”
Section: Current Status Of In Vitro Alternatives To Fish Testsmentioning
confidence: 99%
“…Therefore, more studies are needed to clarify the immunotoxicological effects and mechanisms of heavy metals in fish leucocytes. Furthermore, this kind of approximation could be helpful in fish immunotoxicology and should be explored, moreover with the knowledge that in vitro cytotoxicity assays with fish cell lines are very well correlated to acute lethality tests in vivo (Segner, 2004). Taking in consideration all the previous data, the aim of this work was to evaluate the immunotoxicological effects of four heavy metals (Cd, As, Pb and Hg) on the head-kidney leucocytes from gilthead seabream (Sparus aurata), the most important farmed fish species in the Mediterranean area.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent economic and ethical constraints associated with in vivo tests using live animals for cytotoxicity analysis have led to the preferred utilization of in vitro biological test systems such as cell lines derived from aquatic animal species (Keddy et al 1995;Mátlová et al 1995;Huuskonen et al 1998;Segner 1998;Olabarrieta et al 2001;Repett et al 2001;Choi and Oris 2003;Ní Shúilleabháin et al 2004;Segner 2004;Wang et al 2004;Gűlden et al 2005 ) commonly present and bioavailable in the aquatic environment. This paper describes the employment of the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] and CB (Coomassie Blue) assays for the examination of cytotoxic responses of these turtle cell lines following their exposure to the four selected metal salts.…”
Section: Introductionmentioning
confidence: 99%